Comparing nivolumab response between smokers and ex-smokers in advanced non-small cell lung cancer: It is never too late to quit smoking - Ersoy, Mustafa (The European Research Journal, 2025)
Objectives: Lung cancer is most commonly caused by smoking, and unfortunately, a significant portion of patients continue to smoke even during their treatment. Our study aimed to investigate the impact of current smoking on the treatment response in patients receiving nivolumab. Methods: This was a retrospective cohort study that compared the treatment responses of patients who continued to smoke during nivolumab therapy and those who had a history of smoking but had quit prior to nivolumab initiation. The study included 55 patients with advanced non-small cell lung cancer who received treatment between 2019 and 2025. All participants had stage 4 disease and had progressed after initial platinum-based combination chemotherapy. The treatment responses were categorized as progressive disease, stable disease, partial response, and complete response, and the differences between current smokers and ex-smokers were analyzed, with the response evaluation conducted according to the PET Response Criteria in Solid Tumors 1.0 guidelines. Results: The analysis revealed a statistically significant difference in treatment response between ex-smokers and current smokers (P=0.039). Ex-smokers demonstrated superior Objective Response Rates (56.0% vs. 25.0%) and Disease Control Rates (76.0% vs. 33.3%) compared to current smokers, with the difference in Disease Control Rate reaching statistical significance (P=0.042). Furthermore, multivariate logistic regression indicated that current smokers were 3.64 times less likely to achieve an objective response to nivolumab than ex-smokers, a finding that, while borderline significant, suggests a clinically meaningful trend (P=0.084). Conclusions: Our study demonstrated that continued smoking during nivolumab therapy may negatively impact the treatment response. While more prospective data is needed, the current results and existing literature suggest that smoking cessation is crucial for patients receiving nivolumab, and clinicians should be more vigilant in addressing this issue.